Pertimbangan Hakim PERTIMBANGAN HAKIM DALAM PENETAPAN DISPENSASI KAWIN (Tinjauan Aspek Filosofis, Yuridis, dan Sosiologis): Diskripsi kasus dan Pertimbangan Hakim dalam Penetapan Dispensasi Kawin di Pengadilan Agama Bogor - Fitriyani; Sudirman L. (Al-Mizan (e-Journal), 2023)
This study aims to find out the description of the case and the judge's considerations in determining the Bogor Religious Court with case Number 54/Pdt.P/2021/PA.Bgr. The research questions namely: 1) how is the case for dispensation of marriage at the Bogor Religious Court? 2) how to analyze the judge's considerations in determining the dispensation of marriage in terms of philosophical, juridical, and sociological aspects. This study uses a qualitative descriptive analysis method. Source of data using primary and secondary. Data collection techniques with interviews, observation, and documentation. This study uses a study of the theory of judges' considerations in the determination of religious courts, which has determined that the determination of judges must consider philosophical, juristic, and sociological aspects, so that the justice to be achieved, realized, and accounted for in the determination of judges. The results of the study show that: First, the judge's consideration in granting a marriage dispensation as per Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage, where the age of a man and a woman must reach the age of 19 (nineteen) years. So to carry out their marriage, the petitioners must obtain a marriage dispensation permit from the court by the provisions of Article 7 paragraph (2) of the Marriage Law; Second, the Bogor Religious Court granted permission for a marriage dispensation because the applicants already had a very close relationship, so things that were prohibited by religion and laws and regulations did not happen.